'Hooks' and 'Anchors' for relational ecosystem-based marine management. (August 2021) - Macpherson, Elizabeth; Urlich, Stephen C.; Rennie, Hamish G.; Paul, Adrienne; Fisher, Karen; Braid, Laura; Banwell, Jill; Torres Ventura, Julia; Jorgensen, Eric
Abstract: There remains uncertainty about the legal and policy tools, processes and institutions needed to support ecosystem-based marine management (EBM). This article relies on an interdisciplinary study of ecosystem-based language and approaches in the laws and policies of New Zealand, Australia and Chile, which uncovered important lessons for implementing EBM around the need to accept regulatory fragmentation, provide effective resourcing, respect and give effect to Indigenous rights, and avoid conflating EBM with conventional approaches to marine spatial planning. We suggest a new way of thinking about EBM as a 'relational' process; requiring laws, policies and institutions to support its dynamic process of dialogue, negotiation and adjustment. We argue that relational EBM can be best supported by a combination of detailed rule and institution-making ( hooks ) and high-level norm-setting ( anchors ). With its focus on relationships within and between humans and nature, relational EBM may enable new ways to secure cross-government collaboration and community buy-in, as well as having inbuilt adaptability to the dynamics of the marine environment and the impact of climate change at different scales.